O odantroponimicznych nazwach dzierżawczych, rodowych i patronimicznych w świetle etymologii ludowej polskich toponimów - Rogowska-Cybulska, Ewa (Slavia Occidentalis, 2014)
The article presents–on the selected examples–the functioning of the possessive, ancestral and patronymic names derived from anthroponyms in the process of morphological reinterpretation of Polish toponyms. Its first part treats of toponyms which, according to onomasts belong to possessive, ancestral and patronymic names, and 122 Ewa Rogowska-Cybulska SO 71/1 folk etymologists move them to other semantic classes. In the second part of the article, the author discusses the toponyms which have been classified as possessive, ancestral and patronymic names by non-scholarly etymology, regardless of the fact to which groups they belong according to scholarly etymology. In this part, the types of folk etymologies have been classified according to the degree of discrepancies of their results and the results of scholarly etymologies. Three major groups of the studied pseudoetymologies have been isolated: folk explanations deriving toponyms from bases belonging to a different word formation core than their real base w rd (e.g., Rogoźna, Łoje, Lublin); motivations by anthroponyms belonging to the same word formative core as the real nominative base (e.g., Wiślica, Łoje, Brzostowo, Obrytki, Sierzputy, Zebrzydowice, Boguszki, Pawełki, Szczepankowo); pseudoetymologies deriving toponyms from the same anthroponyms as the scholarly etymologies but possessing a different semantic interpretation (e.g., Chrzanów, Celestynów, Matysówka, Wszebory).